El padre Juan J. Delgado, creador de la etnohistoria y etnobotánica en Filipinas - Cabrero, Leoncio (Revista Española de Antropología Americana, 2003)
Father Juan J. Delgado was a missionary in the Philippines for fifty years and wrote a great work, La Historia General Sacro-Profana, Política y Natural de las Islas de Poniente llamadas Filipinas. This book was finished at 1751. The third and fourth books are about ethnography and ethnobotany. Some parts of them are discussed in this paper.
Keywords: Father Delgado; Philippines; Ethnography; Ethnobotany